2020
DOI: 10.1002/psp4.12571
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Physiologically‐Based Pharmacokinetic Models of Rosuvastatin

Abstract: Physiologically‐based pharmacokinetic (PBPK) modeling is increasingly used to predict drug disposition and drug–drug interactions (DDIs). However, accurately predicting the pharmacokinetics of transporter substrates and transporter‐mediated DDIs (tDDIs) is still challenging. Rosuvastatin is a commonly used substrate probe in DDI risk assessment for new molecular entities (NMEs) that are potential organic anion transporting polypeptide 1B or breast cancer resistance protein transporter inhibitors, and as such, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Bowman et al recently summarized the rosuvastatin PBPK models reported in the literature and reviewed the current gaps. 31 These earlier studies evaluating rosuvastatin DDIs via PBPK primarily focused on hepatic OAT1B‐based interactions with inhibitors, such as rifampicin and cyclosporine 31 , 32 ; and we are not aware of any reports describing PBPK model performance for BCRP‐based interactions extensively. The rosuvastatin DDIs assessed here primarily involve BCRP inhibition (capmatinib, darolutamide, fenebrutinib, fostamatinib, elbasvir/grazoprevir, and velpatasvir).…”
Section: Discussionmentioning
confidence: 99%
“…Bowman et al recently summarized the rosuvastatin PBPK models reported in the literature and reviewed the current gaps. 31 These earlier studies evaluating rosuvastatin DDIs via PBPK primarily focused on hepatic OAT1B‐based interactions with inhibitors, such as rifampicin and cyclosporine 31 , 32 ; and we are not aware of any reports describing PBPK model performance for BCRP‐based interactions extensively. The rosuvastatin DDIs assessed here primarily involve BCRP inhibition (capmatinib, darolutamide, fenebrutinib, fostamatinib, elbasvir/grazoprevir, and velpatasvir).…”
Section: Discussionmentioning
confidence: 99%
“…measurements and biological activities. [103][104][105][106][107][108][109][110][111][112][113][114] In some cases, the experimental logP N , pK a, and log P app IP were reported, but otherwise they were determined using ChemAxon. The LipE was then simulated using Equation 1 and Equation 2 and compared to their experimental values.…”
Section: Experimental Data Of Lipophilicity-based Applications and Me...mentioning
confidence: 99%
“…This is already evident for biomarkers like CPI, NMN, and PDA and no doubt that future efforts will encompass others like TAU, GCDCA-S, and IBC. 5,[78][79][80][81][82][83][84][85] Further progress will require the refinement of PBPK model compound files for each biomarker, which will necessitate the acquisition of basic information (e.g., BPR, renal FR, synthesis rate, turnover, and ft). In this regard, it is important to understand that SLC biomarker PKs and response to perpetrator drugs may be impacted by disease, organ impairment, (epi)genetics, gender, pregnancy, age, smoking, food intake, exercise, diurnal effects, and any myriad of other factors that might modulate their formation and clearance.…”
Section: Pbpk Modeling Applied To Slc Biomarkersmentioning
confidence: 99%
“…It goes without saying, that the development, validation, and use of PBPK models for SLC biomarkers will continue to loom large, as will their integrated use with models describing the PK profile of transporter probe drugs (e.g., furosemide, rosuvastatin, and metformin) to support IVIVE. This is already evident for biomarkers like CPI, NMN, and PDA and no doubt that future efforts will encompass others like TAU, GCDCA‐S, and IBC 5,78–85 . Further progress will require the refinement of PBPK model compound files for each biomarker, which will necessitate the acquisition of basic information (e.g., BPR, renal FR, synthesis rate, turnover, and ft).…”
Section: Moving Forwardmentioning
confidence: 99%
See 1 more Smart Citation